Technique and safety aspects of resistance exercises: A systematic review of the literature - Colado, J. C.; Garcia-Masso, X. (The Physician and Sportsmedicine, 2009)
Abstract: A systematic review of the scientific literature was conducted to identify the optimal ranges of motion for preventing injury in the main joints of the body during resistance exercise performance. These ranges of motion are independent of the type in which the resistance exercises could be applied (ie, adults, elderly, athletes, recreational exercisers), and the regions examined include the shoulder, spine, and knee, which are injured most often. It can be concluded that during the performance of any resistance exercise, it is possible to put anatomical structures at risk with certain body positions; therefore, it is necessary to understand these movements so injury can be avoided.